Sexual lives of reproductive-aged people with disabilities in Central Sidama National Regional State, Ethiopia: a mixed-methods study - Zelalem Tenaw; Taye Gari; Achamyelesh Gebretsadik (BMC, 2023)
Abstract Background Sexuality is an important part of human life; people with disabilities have the same sexual desires as people without disabilities. However, the status of the sexual lives of reproductive-aged people with disabilities is unfolded in Ethiopia. Therefore, this study was aimed to assess sexual lives and its associated factors among reproductive-aged people with disabilities in central Sidama National Regional State, Ethiopia. Methods A mixed-methods study was conducted among randomly selected 685 reproductive-age people with disabilities and fifteen (15) in-depth interviews among individuals who have sexual practice experience from June 20 to July 15, 2022. The quantitative data were collected through face-to-face interviewing techniques using a structured and semi-structured questionnaire. A multilevel logistic regression analysis model was employed to analyze the data. The adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to report the measures of associations. The qualitative data were managed and analyzed using the phenomenological research analysis approach. Results In this study, 59.9% (95% CI: 56.1, 63.5) of the people with disabilities have practiced sexual intercourse. Of these, 30.8% (95% CI: 27.4, 34.4) were males and 29.1% (95% CI: 25.7, 32.6) were females with disabilities. Being female (AOR = 2.81; 95% CI: 1.70, 4.62), having an occupation (AOR = 7.55; 95% CI: 4.03, 14.1), having a disability and being in a wheelchair (AOR = 0.27; 95% CI: 0.09, 0.82), having a good self-perception (AOR = 0.46; 95% CI: 0.28, 0.77), and having a rich economic status (AOR = 2.05; 95% CI: 1.08, 3.89) were factors associated with the sexual practice. The qualitative findings revealed that having sexuality information (training) is the facilitator, and community discrimination and low economic income are the barriers to sexual practice. Conclusion Sexual practice among people with disabilities is low in the Dale and Wonsho districts and Yirgalem city administration. Socio-demographic and economic factors and sexuality training are the associated factors. Therefore, creating job opportunities and economic empowerment, providing sexuality training, and creating community awareness are crucial to improving the sexual practice of reproductive-age people with disabilities.